2020
DOI: 10.1186/s12909-020-02194-2
|View full text |Cite
|
Sign up to set email alerts
|

Burnout level and associated factors in a sub-Saharan African medical setting: prospective cross-sectional survey

Abstract: Background Burnout in the hospital environment is a problem that affects care and training. Often explored in the high-income medical context, burnout is poorly studied in low and middle-income countries characterized by a precarious hospital situation and a high stake linked to the Millennium Development Goals. The aim of our study was to determine in medical practitioners, in a sub-Saharan African country’s medical context, the burnout level and associated factors. Methods A prospective cross-sectional stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A total of 42 (76.3%) studies used an MBI scale composed of 22 items [ 21 - 32 , 34 - 39 , 41 , 42 , 45 , 46 , 48 - 58 , 60 , 62 - 64 , 66 , 68 , 69 ,​ 71 , 72 ]. Additionally, 11 (20%) studies did not describe which MBI items were used [ 33 , 43 , 47 , 59 , 61 , 65 , 68 , 70 , 73 - 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 42 (76.3%) studies used an MBI scale composed of 22 items [ 21 - 32 , 34 - 39 , 41 , 42 , 45 , 46 , 48 - 58 , 60 , 62 - 64 , 66 , 68 , 69 ,​ 71 , 72 ]. Additionally, 11 (20%) studies did not describe which MBI items were used [ 33 , 43 , 47 , 59 , 61 , 65 , 68 , 70 , 73 - 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Answers to the MBI were distributed on a Likert-type scale, and most studies used a 0 to 6 score (26/55, 47.2%) [ 21 , 23 - 25 , 28 , 30 - 32 , 36 , 37 , 41 - 44 , 48 , 49 , 51 , 54 , 57 - 59 , 62 , 64 , 66 , 67 , 69 , 74 ]. A total of 16 (29%) studies did not describe how they rated the scores [ 22 , 27 , 33 , 38 , 46 , 47 , 50 , 53 , 55 , 56 , 61 , 65 , 68 , 71 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is unsurprising that clinicians carry negative emotions surrounding traumatic patient deterioration events, this finding is critical in our recognition of the profound emotional toll that deteriorating patients have on clinicians. This emotional toll contributes to increased moral distress, clinician burnout and higher staff turnover in both highand limited-resource settings (11,21). The fact that participants across all disciplines at both hospitals discussed negative emotions also demonstrates how widespread and universal these responses are in the context of patient deterioration and critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study displayed a moderately high prevalence of burnout in Tanzanian physicians. A recent study from Central Africa similarly showed that almost 50% of surveyed practitioners manifested burnout, displaying the magnitude and scope of this problem on the African continent [ 3 ].…”
Section: Discussionmentioning
confidence: 99%